Quasi static mechanical study of vacuum bag infused bouligand inspired composites - Amorim, Luís Manuel Machado (2021)
Three novel Bouligand inspired composites were produced by vacuum bag infusion manufacturing process and their quasi-static mechanical performance were compared to a conventional aircraft laminate. A morphologic/physical study was first conducted for all configurations and their mechanical response under tensile, three-point bending (3-PB) and interlaminar shear strength (ILSS) tests were then evaluated and discussed. No significant number of voids were detected into laminates, however, a rough and poor defined interlaminar region was observed in both Bouligand-like configurations. Under quasi-static mechanical solicitations, and when compared to reference layup, bioinspired configurations have shown similar and 18% higher tensile and flexural modulus. However, the progressive and translaminar failure mode, typically observed in these configurations, led to a lower load bearing capability. Despite presented similar interlaminar resistance than reference, finite element models built have revealed a good correlation between cross-section stress field and failure mode observed experimentally.